STUDY ON PROBLEMS PERCEIVED BY THE CARETAKERS ATTENDING TO PATIENTS WITH CANCER - P. SREEDEVI, M. SANDHYA RANI, NASREEN BANU and (The Journal of Research, PJTSAU, 2017)
Becoming a parent, is one of the most powerful of the human experiences, is often accompanied with feelings of celebration and relief, but it can also be a time of anxiety, and stress. The term â€œParentingâ€ is derived from the Latin root pario, meaning life-giver, and encompasses much more than just the care giving activities parents perform.